A plan for conversion of stormwater to groundwater recharge on the Utah Valley University main campus, Orem, Utah - Dastrup, Dylan B., author; Ferreira, Gabriela R., author; Zacharias, Daniel, author; Natter, Daniel H., author; Kellum, Lawrence T., author; Emerman, Steven H., author; Davis, Brandon B., author; Alexander, Michael R., author; Selck, Jeff, author; Colorado State University, publisher (Colorado State University. Libraries, 2013)
At the present time the vast majority of the stormwater generated on the Main Campus of Utah Valley University is exported to Utah Lake, which is only 1.4 miles from campus. Although there is a large boulder-lined detention pond on campus, it is used only as a holding pond before the stormwater is exported. The objective of this study was to determine what percentage of the average annual stormwater and the stormwater generated by a 100-year 24-hour precipitation event could be retained on campus and used for groundwater recharge by constructing a series of French drains. It was determined that the Main Campus could be divided into 33 watersheds that currently export stormwater (72.8% of the surface area) and 28 additional self-contained watersheds. Using the NRCS Runoff Curve Method, it was determined that the Main Campus exports 0.4998 ac·ft of stormwater annually and would export 23.2969 ac·ft of stormwater following a 100-year 24-hour precipitation event, while the self-contained watersheds capture 0.0330 ac·ft annually and would capture 2.7913 ac·ft following a 100-year 24-hour event. The construction of nine French drains (including subsurface expansion of the existing detention pond with discontinuation of pumping) with a combined surface area of 0.9260 ac would convert to groundwater recharge 0.1402 ac·ft annually (28.1% of current export) and 6.2083 ac·ft following a 100-year 24-hour precipitation event (26.6% of current export). Further reduction of stormwater export could not be accomplished without disruption to current paved areas or other built infrastructure.
Hydrology days 2013
AGU hydrology days 2013
2013 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2013.